First results of the biostratigraphy and geochronology of the classic Nihewan Fauna, China - Farjand, Arya; Zhang, Zhaoqun; Gibbard, Philip L.; Bi, Shundong (Frontiers in Earth Science, 2023)
The Nihewan Basin is infilled by a relatively complete Pliocene to Pleistocene sequence, rich mammalian fossils and containing many Palaeolithic artefacts, implying that it is a unique location for Quaternary multidisciplinary study. Fossil excavations in these deposits have been carried out for nearly a century. The systematic study of the fossils by Teilhard de Chardin and Piveteau in 1930 laid the foundations for the classic Nihewan Faunal assemblage, which has been widely followed as a standard for the Early Pleistocene biochronology in eastern Asia. With the availability of magnetostratigraphic analyses on several sections in the Nihewan basin, a comprehensive geochronological study is timely pending. Here we report the results of a comprehensive survey of the Xiashagou section, where the classic Nihewan Fauna was discovered. By synthesising the lithostratigraphical, biostratigraphical, and magnetostratigraphical information, together with measurements taken by the authors, the total thickness of the Nihewan Formation in the Xiashagou section being 116 metres. Furthermore, the geochronological study demonstrates that the classic Nihewan Fauna was originally recovered from at least 6 fossil horizons, spanning from ~2.4Ma to ~1.8Ma, i.e., the early Early Pleistocene. The new evidence from the Xiashagou section also suggests several cycles of fluctuations in the biodiversity and population of the classic Nihewan Fauna during the early Pleistocene. The preliminary correlation of these cycles matches the short periods of glaciation in the early Pleistocene.